Monochorionic twins with unequal placental sharing: why can the outcome still be favorable?. (17th April 2016) - Sun, Lu-Ming; Li, Ying; Zou, Gang; Zhou, Fenghe; Lei, Xiaoping; Cram, David S.; Oepkes, Dick; Wu, Junqing
Abstract: Objective : In monochorionic diamniotic (MCDA) twin pregnancies, unequal placental sharing does not always lead to adverse outcomes. The aim of this study is to investigate how unequal placental sharing may be compensated by placental anatomical changes. Methods : Between January 2012 and July 2013, a total of 60 uncomplicated MCDA pregnancies ending in live birth of healthy twins were studied. Placentas were divided into two groups; an equally shared placenta group (placenta territory discordance ≤25%, N  = 40) and an unequally shared placenta group (placenta territory discordance >25%, N  = 20). Angioarchitecture, cord insertion type and the distance between two cord insertions were compared. Results : Vascular anastomoses were seen in all 60 placentas, and 58 placentas (96.7%) had arterioarterial anastomoses (AA). The overall diameter of the AA was larger in the unequally shared placenta group as compared to the equally shared placentas (0.27 ± 0.12 cm versus 0.19 ± 0.1 cm, p  < 0.05). The distance between the cord insertions was shorter in the unequally shared group (14.5 ± 6.0 cm versus 18.3 ± 6.5 cm, p  < 0.05) . Conclusion : The absence of adverse outcomes in unequally shared placenta group can be explained by the presence of large AA and shorter distance between cord insertions, protecting the twin with the smaller placental part against growth restriction and other pathology.